Authority and the individual - Russell, Bertrand (London, 2005)
In Authority and the Individual we discover Russell at his best and most characteristic. With clarity and deep understanding Russell tackles the perennial questions about the balance between authority and human freedom: the formation and purpose of society, justice, education, moral evolution, and social, economic and intellectual progress. He brings these issues to life with a wealth of illuminating examples ranging from Ancient Greek democracy and the French Revolution to the modern welfare state.
Keywords: Social structure